MANAJEMEN KEUANGAN BERBASIS E-RKAM DALAM MENINGKATKAN MUTU PENDIDIKAN MADRASAH DI KOTA BALIKPAPAN - Sinta Ningsih; Mohammad Salehudin; Agus Setiawan (STKIP PGRI Situbondo, 2023)
The aim of the research is to describe e-RKAM-based financial management in improving the quality of Madrasah education in Balikpapan City. To analyze the inhibiting and supporting factors for E-RKAM-based financial management in improving the quality of Madrasah education in Balikpapan City. This type of research is descriptive qualitative with a phenomenological approach. Research location at MTs Negeri 1 and MTs Negeri 2 and MTs Ibnu Khaldun Balikpapan. Data collection techniques are observation, interviews and documentation. The analysis technique uses the Milles Huberman and Saldana model which includes data collection, data presentation, condensation and conclusions. The data validity test was carried out using triangulation. The result of this research is to find that e-RKAM-based financial management in improving the quality of Madrasah education in Balikpapan City has been implemented according to the stages and elements of the financial management function which includes planning, implementation, organizing and monitoring or evaluating. According to the instrument, the quality of madrasah education can be improved by running a budget according to the needs of the madrasah, the quality of education is carried out in accordance with the vision and mission of the madrasah and to achieve the goals of the madrasah, realizing improvements in madrasah facilities and infrastructure by creating transparency in madrasah financial management. Meanwhile, the findings of the obstacles and supporting factors for E-RKAM-based financial management in improving the quality of Madrasah education in Balikpapan City, are that the obstacle factors include operators who do not properly understand the E-RKAM application and must take part in training or outreach activities, limited infrastructure and facilities. which needs to be fought for in budgeting, the quality of teaching staff and educational staff. Meanwhile, the supporting factors for financial transparency and accountability are between kamad, head of TU, treasurer, operators and other staff. Kamad and related staff take part in upgrading, there are improvements to support all financial transparency and accountability between kamad, head of TU, treasurer, operators and other staff.